Leaf appearance of annual clovers responds to photoperiod atemergence - H., Nori; D.J., Moot; A.D., Black (Elsevier B.V., 2016)
Leaf appearance rate and time to canopy expansion of four annual clover species (arrowleaf, balansa,gland and Persian) were quantified in field and controlled environment studies. Crops sown in autumn,which experienced shortening daylengths at emergence, had a slower rate of leaf production and con-sequently took a longer time to initiate branching, than spring-sown crops. When autumn-sown ‘Bolta’balansa clover emerged on the shortest day in winter (21 June), the rate of leaf appearance was lengthenedby 4◦C d/leaf/h. When the same species emerged after the shortest day, into an increasing photoperiod,the phyllochron was shortened by 5◦C d/leaf/h. This influence of photoperiod on the phyllochron conse-quently altered the time to axillary leaf production (branching). Throughout all sowing dates, phyllochronwas the fastest for ‘Prima’ gland (33–91◦C d/leaf) and slowest for ‘Cefalu’ arrowleaf (53–116◦C d/leaf)clovers. ‘Bolta’ balansa was 44–82◦C d/leaf and ‘Mihi’ Persian 61–93◦C d/leaf. The response of phyllochronto photoperiod suggests these annual clovers should be sown in late summer or early autumn to initiateaxillary leaf production as soon as possible to ensure maximize dry matter for early spring.